Oxygen deficiency in Sr2FeO4−x: electrochemical control and impact on magnetic properties. Issue 28 (6th July 2022) - Adler, Peter; Schröder, Liane; Teske, Klaus; Reehuis, Manfred; Hoser, Andreas; Merz, Patrick; Schnelle, Walter; Felser, Claudia; Jansen, Martin
Abstract : Oxygen was extracted from the layered iron(iv ) oxide Sr2 FeO4 using an electrochemical method. The resulting oxygen-deficient Sr2 FeO4− x materials exhibit complex magnetism with coexistence of spiral order and magnetic clusters. Abstract : The oxygen-deficient system Sr2 FeO4− x was explored by heating the stoichiometric Fe 4+ oxide Sr2 FeO4 in well-defined oxygen partial pressures which were controlled electrochemically by solid-state electrolyte coulometry. Samples with x up to about 0.2 were obtained by this route. X-ray diffraction analysis reveals that the K2 NiF4 -type crystal structure (space group I 4/ mmm ) of the parent compound is retained. The lattice parameter a slightly decreases while the c -parameter increases with increasing x, which is in contrast to the Ruddlesden–Popper system Sr3 Fe2 O7− x and suggests removal of oxygen atoms from FeO2 lattice planes. The magnetic properties were studied by magnetization, 57 Fe Mössbauer, and powder neutron diffraction experiments. The results suggest that extraction of oxygen atoms from the lattice progressively changes the elliptical spiral spin ordering of the parent compound to an inhomogeneous magnetic state with coexistence of long-range ordered regions adopting a circular spin spiral and smaller magnetic clusters.